Extra-capsular Parotid Tumor Dissection - B. R. Sathyakrishna; Santosh Singh Rajaput (International Journal of Medical Research and Review, 2016)
Parotid tumors are one of the common conditions in surgical practice and gold standard procedure for benign tumors of parotid being superficial parotidectomy but with risk of complications like facial nerve injury,whereas, in extra-capsular dissection of parotid, surgeon performs a careful dissection of the tumor and spares the handling of facial nerve thereby minimizing chances of facial nerve injury. We present here a case of benign parotid tumor operated by extra-capsular dissection.